MAGNETIC RESONANCE IMAGING APPARATUS - HOSHINO SHIN (2005)
PROBLEM TO BE SOLVED: To reduce magnetic interference between an RF coil and a shim coil to keep the RF coil performance in the magnetic resonance imaging apparatus, and to appropriately apply a high frequency magnetic field by an RF coil to a subject to be examined. SOLUTION: The RF coil, a gradient magnetic field coil, and the shim coil are arranged in order from the measuring space side, in which the subject to be examined is arranged, to the apparatus side for generating a static magnetic field, and an RF shield for shielding the high frequency magnetic field is inserted between the gradient magnetic field coil and the shim coil, or only a component coil which magnetically interferes with the RF coil in the shim coil is arranged at the outside (the apparatus side for generating the static magnetic field) of the RF shield. Furthermore, an LC parallel circuit, which has a high impedance only in the frequency of the high frequency magnetic field generated by the RF coil, is inserted in a place at which the upper and lower shim coils connect in series. COPYRIGHT: (C)2005,JPO&NCIPI